Wallaceochromis gen. nov, a new chromidotilapiine cichlid genus (Pisces: Perciformes) from West Africa - Lamboj, Anton; Trummer, Franziska; Metscher, Brian D. (Zootaxa, 2016)
A new genus, Wallaceochromis, is described for the chromidotilapiine cichlids of the Pelvicachromis humilis group. It differs from Pelvicachromis sensu stricto in the number and arrangement of tubular infraorbitals, a straighter and sloping dorsal head profile with a low supraoccipital crest, higher abdominal vertebral counts (14–15 vs. 13–14), and in displaying a pattern of vertical bars on the body in several behavioral situations.